OPTIMASI PERENCANAAN PRODUKSI KERAJINAN ROTAN DI ANGGA FURNITURE MENGGUNAKAN LINEAR PROGRAMMING - Tiara Vania; Rara Sandhy Winanda (LPPM Universitas Bina Bangsa, 2024)
Production planning is an activity to obtain products in accordance with the needs of two parties, namely companies and consumers. Production planning is important in the industry in order to achieve optimal profits. In the rattan handicraft business, furniture faces problems in production planning. The production process is carried out based on the availability of raw materials and the estimated average demand, but it is often difficult to determine the optimal amount and time of production. This results in a shortage or excess of stock which has an impact on profits. By using a linear program, this study aims to determine the optimal results in production planning in the rattan and furniture handicraft business using the simplex method so that optimal profits are obtained. The results showed that the number of products produced was optimal so that the profit obtained was 8.49%.